Editorial - Fernando, Marrisa (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
Editorial Maria Socorro (Marrisa) Fernando, PhD Editor in Chief This issue of the ABAC ODI Journal Vision. Action. Outcome. presents ten articles on various topics highlighting change management in various contexts . There are seven action research papers that present organization development interventions . Phunthasaen and Chungviwatanant present a comprehensive action research using OD interventions to enhance perceived organization support, supervisor feedback environment, supervisory communication and trust to improve supervisor-subordinate relationships in a Dessert Café and Restaurant, Phi Phi Island, Thailand. Li and Kim present a paper “ To Enhance Non-English Major Students’ English Communicative Competence by Improving Students’ English Learner Autonomy through Organization Development Interventions—An Action Research at Zhejiang Yuexiu University of Foreign Languages (ZYUFL) in China”. The research paper analyzed the impact of organization development interventions (ODIs) on learner autonomy (LA) and communicative competence (CC) of non-English major students in ZYUFL, Zhejiang, China. The research “ Enhancing Student Class Engagement by Improving Students’ Self-efficacy and Motivation through Organizational Development Interventions — A Case Study of Zhejiang Yuexiu University of Foreign Languages in China” by Huang states that self-efficacy and motivation can be used to improve student class engagement, and in order to achieve sustainable change, further actions should be carry out to have a greater impact on the long-term development. The article of Chen and Vinitwatanakhun on “Improving Students’ Career Decision Making through Organization Development Interventions—A Course Design of Career Exploration in the International College of Zhejiang Yuexiu University of Foreign Languages” aims to improve students’ career decision making in terms of career decision making self-efficacy (CDMSE) through organization development interventions (ODI) based career exploration course. The article “To Improve Employee Career Success through Organizational Development Intervention: An Action Research of AIA Co., LTD. Changzhou Branch” by Lin and Kim used the results of the study to design an improvement framework to help individuals improve their career competency, emotional intelligence and self-efficacy and to achieve career success and better career development in an uncertain borderless career period. The article by Feng and Kim titled “ Enhancing Teaching Effectiveness to Foster Student Academic Motivation and Student Engagement in the EFL Classroom through Organization Development Interventions: An Action Research of Zhejiang Yuexiu University of Foreign Languages in China” focused on enhancing teaching effectiveness to foster student academic motivation and engagement in the EFL classroom by implementing ODI. The study on “ Enhancing the Middle Management at Individual Level for Organizational Change of an International Airline in Asia” by Bhitakburi confirms the relationship between perspective of change, commitment to service and loyalty to organization is related and it affects attitudes towards organizational change. Three articles are empirical research on various situations of internal or external stakeholders of their workplaces and the society. The article titled “ An Investigation of Eldercare Practices in Thailand through Institutional Logics Lens” authored by Phayungphong aims to unfold the compelling logics that shape collective norms and behaviors, and to collect empirical evidence on how the changing context of the Thai family structure is affecting the geriatric and long-term care industry in Thailand. Chumpong and Chuai-in present a study “ The Use of English Language in Tourism Workplaces in Pakmeng Beach Area,Trang Province” . This research used purposive sampling to explore English language skills used by front desk staff in tourism workplaces in Pakmeng beach, Trang province, Thailand ; to identify the frequency of English languages skills used by the front office staff in tourism workplaces; and to investigate the interests and needs in improving English language skills by front office staff. The article of Sitsira-at on “ AQ and EQ Related to Lifelong Learning of Undergraduate Students” presents the correlational comparative study to investigate the importance of adversity quotient and emotional quotient as related to lifelong learning and finding the predictors of lifelong learning of undergraduate students. We are grateful to our authors who have extensively conducted research and publication . Your publications contribute to knowledge sharing and building up further research and development that generates innovation, capacity building , and sustainability.